STUDI KEMUNGKINAN PERUBAHAN STATUS DESA TELUK KAPUAS MENJADI KELURAHAN DI KABUPATEN KUBU RAYA - Murtir Jeddawi; Abdul Rahman; m. nawawi (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2018)
The purpose of this study is to explain whether the plan to change the status of Teluk Kapuas village into kelurahan in district of Sungai Raya Kabupaten Kubu Raya is feasible and meets the requirements in terms of philosophical, sociological and juridical aspects. The research method used in this research is Descriptive method with normative and empirical juridical approach by using secondary data and primary data which analyzed qualitatively. Methods of data collection from this study are interviews, observations, and documentation studies in the form of proposals of pemekaran desa and others. Techniques to establish data validity are: credibility, transferability, dependability, and confirmability. Data analysis technique used in this research is data analysis technique model of Miles and Hubberman that is data reduction, display data and withdrawal conclusion. The results showed that: the philosophical, sociological, and jurisdiction of Teluk Kapuas Village based on the requirements established by Law no. 6/2014 on the Village and administrative requirements set forth in the Minister of Home Affairs Regulation no. 1/2017 on Village Arrangement has been fulfilled and deserves to change status to kelurahan